Optimal policy for macro-financial stability - Gianluca Benigno; Huigang Chen; Christopher M. Otrok; Alessandro Rebucci; Eric R. Young (Federal Reserve Bank of New York, 2019)
There is a new and now large literature analyzing government policies for financial stability based on models with endogenous borrowing constraints. These normative analyses build upon the concept of constrained efficient allocation, where the social planner is constrained by the same borrowing limit that agents face. In this paper, we show that the same set of policy tools that implement the constrained efficient allocation can be used by a Ramsey planner to replicate the unconstrained allocation, thus achieving higher welfare. The constrained social planner approach may lead to inaccurate characterizations of welfare-maximizing policies relative to the Ramsey approach.
Keywords: E61; F38; F44; H23; 330; constrained efficiency; financial crises; macroprudential policies and capital controls; pecuniary externalities; Ramsey optimal policy; social planner